2013
DOI: 10.1093/europace/eut265
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of pulmonary vein antrum isolation in patients with atrial fibrillation: an analysis in regards to substrates and pulmonary vein reconnections

Abstract: The LVZ area was an independent predictor of recurrence after PVAI without any LA substrate modification. Adenosine triphosphate-induced PV reconnection was also an independent predictor, especially in those without LVZs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 30 publications
2
49
3
Order By: Relevance
“…Low‐voltage electrograms are mainly due to atrial fibrosis, and the extent of fibrosis correlates with persistence of AF . In addition, an increased amount of fibrosis in the LA is strongly related to AF recurrence after AF ablation . Fibrotic remodeling tissue acts as an AF substrate because it exhibits slow conduction and short action potential duration, which facilitates reentry .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low‐voltage electrograms are mainly due to atrial fibrosis, and the extent of fibrosis correlates with persistence of AF . In addition, an increased amount of fibrosis in the LA is strongly related to AF recurrence after AF ablation . Fibrotic remodeling tissue acts as an AF substrate because it exhibits slow conduction and short action potential duration, which facilitates reentry .…”
Section: Discussionmentioning
confidence: 99%
“…PVI was performed as previously described . Briefly, ablation of the ipsilateral superior and inferior PVs was performed simultaneously with a continuous lesion around the antral region of the ipsilateral superior and inferior PVs using the open‐irrigation catheter through the SL0 TM or Agilis TM sheath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low voltage in the left atrium, consistent with pre-existent scarring, has been shown to be a powerful predictor of procedural failure in patients undergoing PVI for AF 7,8) . Recent studies have shown that, in comparison to conventional PVI, PVI with the addition of voltage-guided substrate modification achieved by targeting the lowvoltage area is more effective, is safer, and leads to lower proarrhythmic potential [9][10][11][12][13] .…”
Section: La Voltages During Sr and Afmentioning
confidence: 99%
“…A recent study, however, showed no reduction in the AF recurrence rate when either ablation of CFAEs or linear ablation was performed in addition to PVI in patients with PerAF 6) . Pre-existent left atrial (LA) scars indicated by low-voltage zones (LVZs) on 3-dimensional (3D) electroanatomic maps are implicated in suboptimum ablation outcomes 7,8) , and success has been achieved in patients with PerAF when, in addition to PVI, the atrial substrate has been modified by ablation of low-voltage areas detected during sinus rhythm (SR) [9][10][11][12][13] . Slight differences exist between the definitions of such low-voltage zones (LVZs), which are described variously as areas of bipolar voltage of < 0.4 mV ~ < 0.5 mV, depending on the group of investigators [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%